Genetic Interactions during Root Hair Morphogenesis in Arabidopsis - Parker, Jill S. (American Society of Plant Physiologists, 2000)
Root hairs are a major site for the uptake of water and nutrients into plants and form an increasingly important model system for studies of development of higher plants and cell biology. We have identified loss-of-function mutations in eight new genes required for hair growth in Arabidopsis: SHAVEN1 (SHV1), SHV2, and SHV3; CENTIPEDE1 (CEN1), CEN2, and CEN3; BRISTLED1 (BST1); and SUPERCENTIPEDE1 (SCN1). We combined mutations in 79 pairs of genes to determine the stages at which these and six previously known genes contribute to root hair formation. Double mutant phenotypes revealed roles for several genes that could not have been predicted from the single mutant phenotypes. For example, we show that TIP1 and RHD3 are required much earlier in hair formation than previous studies have suggested. We present a genetic model for root hair morphogenesis that defines the roles of each gene, and we suggest hypotheses about functional relationships between genes.